Severe Pneumonia and Human Bocavirus in Adult - Bernd Kupfer; Jörg Janne Vehreschild; Oliver A. Cornely; Rolf Kaiser; Gerhard Plum; Sergei Viazov; Caspar Franzen; Ramona-Liza Tillmann; Arne Simon; Andreas Müller; Oliver Schildgen (2006)
To the Editor: The newly identified human bocavirus (hBoV), a member of the Parvovirus family, is suspected to infect the cells of the respiratory tract and thus may be an etiologic agent of respiratory disease in humans (1). Although Koch postulates have not been fulfilled for HboV, it appears likely to cause a substantial number of respiratory tract infections, at least in children (2,3). We describe a case of severe atypical pneumonia associated with hBoV DNA in a bronchoalveolar lavage (BAL) sample from an adult.